The Influence of Peer-to-Peer Lending Fintech and Payment Gateways on MSME Performance - Prastyatini, Sri Lestari Yuli; Pandia, Salsabilah Putri (Jurnal Manajemen, 2025)
The goal of this research is to find out how much of an impact payment gateways and peer-to-peer lending have on the efficiency of MSMEs in Yogyakarta's Kota Gede. This study will use positivist-based quantitative methods to investigate a preselected community or sample. Kota Gede Yogyakarta Silver MSMEs make up the population studied in this research. One of the most popular tourist attractions and a major cash cow for Yogyakarta is its silver craft, which is why it's important to sample silver MSMEs. This study implemented a purposive sampling technique and had certain criteria for sample selection. For this study 57 MSMEs located in Perak Kota Gede Yogyakarta Silver were surveyed. This research utilized multiple linear regression analysis for its data. The findings indicate that payment gateways and peer-to-peer financing impact the operational efficiency of small and medium enterprises located in Perak, Kota Gede, Yogyakarta substantially. The F test results indicate a substantial difference between the F table value and the F computed value. Apart from the other, both payment gateways and peer-to-peer financing significantly influence the growth of micro, small, and medium enterprises and are regarded as separate independent variables.